Análise de produtores de tomate de mesa do estado de Goiás e uso de Vant como ferramenta para levantamento de informações - Quintanilha, Karolino Torres (2020)
The tomato originates in South America, more specifically in the Andes region, its domestication took place in Mexico. It is a very important vegetable in both the national and international scene and it requires a lot of technology in its cultivation to achieve high yields. For the crop to be competitive in the national scenario, it is essential to know the main systems of the tomato production chain, as well as the profile of the producers and the technologies used. The use of UAV is being tested as a tool for precision agriculture and can be used in large table tomato crops to contribute to some data surveys. Thus, the first chapter of the present study aimed to present a sample of 23 municipalities and the main producers of table tomatoes in the state of Goiás, in order to map and identify the cultivation area of the producers of this crop, as well as to identify the place of production and technologies applied in the field. The data collection was carried out in the years 2018 and 2019, with support from EMATER-GO, LAPIG and UFG, via questionnaires applied on-the-spot and by telephone calls. The second chapter analyzed the profile and production technologies of 15 producers, as well as the feasibility of using UAV as a methodological tool for gathering information. The research is classified as exploratory, qualitative and quantitative. The main tools used for data processing were QGIS and Pix4D. UAV overflights were performed in three different municipalities chosen from the 23 municipalities investigated in the survey. The tools used for data processing were Excel, Word and IBM SPSS. As main results, 99 producers were found, with a total area of 290.27 hectares in 23 municipalities where table tomatoes are produced in the state of Goiás. As for the second trial, it was found that the profiles of the investigated producers are of middleaged people, with good schooling and predominantly male. The technologies applied in the production of table tomatoes follow a pattern with few variations in methods. It was verified that it is possible to use UAV as a methodological tool to assist in the confrontation of information obtained by on-site visits, for this tool is more efficient than satellite images.